Studi Analisis Tentang Resiliensi Terkait Harga Diri dan Sosial Kognitif pada Remaja Panti Asuhan Anak Harapan Samarinda - Rusni Masnina (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background: Adolescence is the period of life of a child who develops into adulthood. Adolescence is often characterized by transitions and changes. Facing his life in the future, adolescents need to have great confidence and hope in order to be able to rise from the difficult conditions and negative emotional experience experienced. For adolescents who live in the orphanage, not having a family or not living with their parents necessarily need to form a strong personality in terms of self-esteem, social cognitive and self-resilience to become adult human beings who are useful and responsible both for themselves and for the people in later.Objectives: This study was aimed to analyze